810 nm Low-intensity laser in the treatment of degenerative articular disease associated with kinesiotherapy and condroprotectors – Case report (Research, Society and Development, 2021)
Degenerative Joint Disease (DJD), also known as Osteoarthritis (OA), is a chronic disease of progressive degeneration for which there is no cure, which can occur in one or more joints in the body, usually caused by overweight of the animal, longevity, instability, incongruence or by injury to the articular cartilage itself. Adult and senile dogs may be affected by this disease as a result of obesity, hormonal disease, natural wear of the joints. In this case, the most affected joint processes are in the pelvic limbs, in the knees and in the hip joint, in the thoracic limbs and in the elbow joints. This work aims to describe the Low Intensity Laser (LIL) efficacy of treatments associated with kinesiotherapy and chondroprotective drugs, performed on a female canine dog affected by this disease in her hip joint and to evaluate this methodology as one of the therapeutic choices more appropriate and less aggressive for the treatment of this disease.